Peri-operative non-surgical determinants of prolonged length of stay following anterior cervical decompression and fusion surgery: a public healthcare perspective - Ella Snowdon; Gokul Raj Krishna; Sayan Biswas; Clementine Wood; Hana Dorey; Hannah Cheng; Rhianne Devlin; Sidharth Suresh; Sayed Farhan Sayed Yaqub Mehdi; Ved Sarkar; K. Joshi George (Perioperative Medicine, 2026)
Abstract Background Prolonged length of stay (PLOS) following anterior cervical discectomy and fusion (ACDF) is associated with increased hospital burden. While surgical and comorbidity-related factors have been widely studied, routinely documented non-surgical and social variables are less consistently reported. This study evaluated univariable associations between these factors and PLOS after ACDF. Methods A retrospective analysis of 1,719 ACDF procedures performed between 2012 and 2022 at a single tertiary centre was conducted. Fifteen preoperative non-surgical and social variables were collected from routine records. PLOS was defined as > = 72 h. Chi-squared tests and unadjusted odds ratios (ORs) were used to evaluate associations with PLOS. No multivariable adjusted model was performed. Results PLOS occurred in 9.89% of cases. Eight factors were associated with post-operative LOS in univariable analysis: age > = 53 years (OR 1.99, p < 0.001), BMI > = 35 (OR 1.66, p = 0.016), ASA grade 3 (OR 4.31 vs ASA grade 1, p < 0.001), male sex (OR 0.64, p = 0.006), limited or aided mobility (OR 3.71, p < 0.001), presence of home social support (OR 0.58, p = 0.0036), chronic pain management issues (OR 3.69, p = 0.014), and recreational drug use (OR 0.23, p = 0.029). Smoking, alcohol use, accommodation type, exercise tolerance, and mental health status were not significantly associated with PLOS. The recreational drug use finding was unadjusted and should not be interpreted as protective. Conclusions Several routinely documented non-surgical and social factors were associated with PLOS following ACDF. These findings are hypothesis-generating and may support preoperative discharge planning. Adjusted analyses including operative level, indication, disease severity, complications and pathway variables are needed before these factors are used for day-case selection.